2021
DOI: 10.14710/ijred.2021.34982
|View full text |Cite
|
Sign up to set email alerts
|

Coal Consumption and Environmental Sustainability in South Africa: The role of Financial Development and Globalization

Abstract: This paper aims to investigate coal consumption and environmental sustainability in South Africa by examining the role of financial development and globalization by using a dataset covering the period from 1980 to 2017. The study utilized the Auto-regressive Distributed Lag Model (ARDL) approach in addition to the Bayer and Hank combined co-integration, fully modified Ordinary least squares (FMOLS), and Dynamic ordinary least Squares (DOLS). The study further utilized the frequency domain causality test to cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…Their outcome elucidated that globalization increases the ecological footprint. Adebayo et al [ 31 ] established that globalization does not affect carbon emissions in South Africa. Likewise, the study of [ 32 ] in Malaysia confirmed that globalization does not affect the ecological footprint.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their outcome elucidated that globalization increases the ecological footprint. Adebayo et al [ 31 ] established that globalization does not affect carbon emissions in South Africa. Likewise, the study of [ 32 ] in Malaysia confirmed that globalization does not affect the ecological footprint.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The data generation phase is reflected in Equation (12). Y t = θ l Z t + e t, e t = β et−1 + e t, (12) where exogenous coefficients is depicted as Z t with ε t. ∼ IID N 0, σ 2 . However, two models namely Fracture, and trend are undertaken in the presence of a structural fracture.…”
Section: Stationarity Testmentioning
confidence: 99%
“…Furthermore, the study of Grossman and Krueger [9] identified positive relationship between economic growth and environmental degradation. Several reports on the trade-off between economic development and environmental destruction have been published, including, Umar et al [10] for China, Adebayo et al [11] for South Korea, Oluwajana et al [12] for South Africa, Khan et al [13] for Pakistan, Usman et al [14] for the United States, Zhang et al [15] for Malaysia, and Adebayo et al [16] for Chile, among others.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the well-established studies, scholars have paid little attention to the influence of hydroelectricity on CO 2 emissions in China. Prior research looked at many pollution factors, such as energy usage and GDP [10][11][12][13][14], urban population [11,[15][16][17][18][19][20], financial development [21][22][23], and trade openness [24][25][26][27][28]. Furthermore, because CO 2 emissions account for more than 76 percent of GHGs emissions, the majority of researchers utilized CO 2 as an indication of degradation of the environment [19,25,28,29].…”
Section: Introductionmentioning
confidence: 99%